Perancangan Visual Workplace Menggunakan Pendekatan 5S Untuk Meningkatkan Efisiensi Komunikasi Visual di Area Produksi PT. XYZ - Wiradarma, Muhammad Visnhu; Wiyatno, Tri Ngudi; Prasetya, Dwi Indra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research aims to design a visual communication system in the production area of PT XYZ using the 5S approach to enhance workplace organization and information clarity. The main issue identified was the absence of structured visual media, such as floor markings, visual SOPs, and tool labeling. A descriptive qualitative method was applied, involving direct observation and interviews with operators and supervisors. The design process included identifying information needs, mapping visual points, classifying media types, and conducting implementation simulations. Results indicate that the 5S-based visual system improves work comprehension, reduces tool search time, and raises safety awareness. It is recommended that the company adopt this design comprehensively to support operational efficiency and a sustainable work culture.